Strategi Pemasaran Usaha Mikro Kecil Menengah (UMKM) di Era Digital - Panjaitan, Suriadi; Lubis, Dessy Masliani Br. (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Marketing strategy is very important for a company because it is a means of achieving company goals. Therefore, small and medium businesses also need to implement marketing strategies. Micro, Small and Medium Enterprises (MSMEs) expand employment opportunities, provide comprehensive economic services to local communities, play a role in smoothing and increasing community income, encouraging economic growth and achieving national goals and achieving the goal of stability. The purpose of this article is to understand the function of marketing strategies, as well as describe the marketing strategies carried out by MSMEs in facing competition in the digital era. This research method uses a qualitative approach with literature studies by collecting and analyzing several relevant articles and books. From this research the author found 3 (three) discussion results, namely (1) revealing understanding of micro, small and medium enterprises (MSMEs), (2) analyzing the function of marketing strategies in entrepreneurship, (3) describing MSME marketing strategies in the digital era.